Greek Higher Education: Old Challenges and the Current Crisis - Dentsoras, Dimitrios (International Higher Education, 2015)
Greek higher education has been facing challenges since well before the current economic crisis. Most importantly, it has been suffering from over-centralization and the infiltration of party politics into most aspects of university life. The current economic crisis provided an opportunity for much needed reforms, but the Greek governments of the past five years failed to provide a convincing long-term plan for modernizing higher education. As a result, reforms were opposed to and eventually abandoned, leaving the Greek universities in their problematic prior state.